Special Guest Editor - Menelaou, Melita (My University, 2026)
Special Issue: “Aerogel Hybrids and Nanocomposites” Journal: Gels (MPDI); Impact Factor: 4.432; Submission deadline: 31/07/2023 Guest Editors: Dr. István Lázár and Dr Melita Menelaou